A method for preparing a self-supporting nanofilm by electrochemical deposition at a gas-liquid interface
Patent Information
- Application Number
- CN202610781011.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-02
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-06-02
AI Technical Summary
虽有研究尝试通过将阴极尖端精确固定于气液或液液界面来强迫沉积,但所得薄膜通常粗糙、厚重(微米级)且面积有限,无法满足现代光电器件对超薄、均匀、大面积薄膜的需求
[0028]The electrochemical system provided by this invention can prepare a uniform self-supporting silver nanofilm at the gas-liquid interface. By simply adjusting the deposition voltage and/or electrodeposition time during the electrochemical deposition process and controlling the voltage waveform during the electrodeposition process, the thickness and roughness of the silver film can be controlled in real time in situ.
Smart Images

Figure CN122327324B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the fields of nanomaterial preparation and electrochemical technology, specifically to a method for preparing self-supporting nanofilms by electrochemical deposition at the gas-liquid interface. Background Technology
[0002] Self-supporting ultrathin nanofilms, especially metallic nanofilms, play an irreplaceable role in fields such as flexible electronics, transparent conductive electrodes, sensors, catalysis, and wearable devices due to their unique mechanical, optical, and electrical properties. However, achieving efficient, low-cost, and large-area fabrication of such films remains a major challenge in this field.
[0003] Currently, mainstream preparation technologies are mainly divided into two categories: The first is "top-down" physical methods, such as magnetron sputtering and evaporation combined with sacrificial layer release. While this method can obtain high-quality thin films, it relies on vacuum equipment, is complex, consumes materials, and the use of sacrificial layers leads to environmental pollution and cost issues. The second is "bottom-up" chemical or assembly methods, such as wet chemical synthesis and Langmuir-Blodgett (LB) technology. Wet chemical methods are difficult to obtain large-area continuous films, while the LB method involves cumbersome steps, slow film formation rates, and often insufficient mechanical strength.
[0004] Electrochemical deposition, as a simple, rapid, and economical material synthesis method, has traditionally only been able to deposit dense films on the surface of solid electrodes. Although some studies have attempted to force deposition by precisely fixing the cathode tip to the gas-liquid or liquid-liquid interface, the resulting films are usually rough, thick (micrometer-scale), and limited in area, failing to meet the demands of modern optoelectronic devices for ultrathin, uniform, and large-area films. The fundamental reason for this lies in the failure to solve the key scientific problem of how to effectively confine metal ions at the interface and guide their preferential nucleation and growth there.
[0005] Therefore, developing a new method that can spontaneously guide the electrodeposition process at the gas-liquid interface to prepare large-area self-supporting ultrathin nanofilms in a one-step, simple, and controllable manner has significant theoretical innovation and practical application value. Summary of the Invention
[0006] The purpose of this invention is to address the shortcomings of existing technologies by proposing a method for preparing self-supporting nanofilms by electrochemical deposition at the gas-liquid interface. By controlling the state of the interface molecular layer through temperature, the method makes it more ordered. The preparation method does not require fixing the cathode at the gas-liquid interface. After applying current, electrochemical growth can be carried out along the single layer of surfactant arranged on the gas-liquid interface. The prepared self-supporting film has a uniform microstructure and adjustable thickness.
[0007] The technical solution adopted in this invention is as follows:
[0008] In a first aspect, the present invention provides a method for preparing a self-supporting nanofilm by electrochemical deposition at a gas-liquid interface, comprising the following steps:
[0009] (1) Prepare an electrolyte containing silver salt and surfactant, and pre-treat the electrolyte by varying the temperature to induce the formation of a metastable solution at the gas-liquid interface;
[0010] (2) Using the pretreated electrolyte as the working medium, a carbon rod as the anode and an aluminum foil as the cathode are immersed in the electrolyte in parallel, and a constant voltage is applied at room temperature to perform electrochemical deposition. The voltage is a constant voltage or a pulse voltage.
[0011] (3) Silver ions are reduced in situ at the gas-liquid interface and spontaneously grow to form a self-supporting nanofilm covering the gas-liquid interface.
[0012] Further, in step (1), the electrolyte is composed of silver nitrate with a final concentration of 25-30 mM and sodium dodecyl sulfate with a final concentration of 10-17 mM.
[0013] Further, in step (1), the electrolyte undergoes temperature-changing pretreatment specifically as follows: the electrolyte is heated to 70~90℃, kept at the temperature until the solution is clear and transparent, and then cooled to 0~5℃ for 15~25 minutes to obtain a translucent or turbid metastable solution with crystals floating at the gas-liquid interface.
[0014] Furthermore, in step (2), the constant voltage is 2-30V and the deposition time is 30-60 seconds.
[0015] Furthermore, in step (2), by setting a pulse voltage waveform that alternates between 5V and 0V, a self-supporting silver nanofilm with a striped microstructure can be obtained, where 5V is defined as the growth voltage, 0V is defined as the stop voltage, the height of the stripes is determined by the application time of the stop voltage, and the width of the stripes is determined by the application time of the growth voltage.
[0016] Furthermore, in the electrochemical deposition process described in step (2), if the voltage waveform is changed during electrochemical deposition, silver films with the following different morphologies are obtained:
[0017] During constant voltage deposition, a self-supporting silver nanofilm with uniform thickness and roughness is obtained, and the area of the silver film increases with the increase of deposition time; when the voltage changes, the thickness and roughness of the silver film change immediately.
[0018] When the applied voltage increases, the growth rate of the self-supporting silver film accelerates, the laterally grown silver film becomes thinner, and the transmittance of the silver film in the visible light band (380 nm-800 nm) increases. When the applied voltage decreases, the growth rate of the self-supporting silver film slows down significantly, the laterally grown silver film becomes thicker, and the transmittance of the silver film in the visible light band decreases. At the same time, a special ridge structure is formed at the growth front of the silver film.
[0019] Specifically, when the deposition voltage suddenly increases from 2V to 5V, the growth rate of the self-supporting silver film increases, and the silver film thickness changes from a sudden decrease to a stable trend.
[0020] Specifically, when the deposition voltage drops sharply from 5V to 2V, the growth rate of the self-supporting silver film slows down significantly. The thickness of the silver film does not increase sharply and then stabilize, but rather increases first, then decreases, and finally stabilizes. A special ridge-like structure appears in the direction perpendicular to the growth of the silver film.
[0021] In a second aspect, the present invention provides a self-supporting nanofilm prepared by the preparation method described in the first aspect.
[0022] Thirdly, the present invention provides a self-supporting nanofilm composite material, comprising the self-supporting nanofilm described in the first aspect, and a substrate supporting the nanofilm; the substrate is selected from silicon wafers, glass sheets, or flexible polymer substrates.
[0023] Furthermore, before the substrate is bonded to the nanofilm, it is treated with oxygen plasma to make its surface hydrophilic.
[0024] Specifically, the substrate was placed in a plasma cleaner and bombarded with medium-power (70-90 W) plasma in an air atmosphere for 10 minutes. The self-supporting silver film grown on the gas-liquid interface was retrieved from the hydrophilic substrate for subsequent research.
[0025] Fourthly, the present invention provides a flexible patch comprising the self-supporting nanofilm described in the second aspect, and a poly(p-phenylene dimethylsiloxane) polymer substrate supporting the nanofilm; the substrate is subjected to oxygen plasma treatment to make its surface hydrophilic before being bonded to the nanofilm.
[0026] Fifthly, the present invention provides applications of the self-supporting nanofilms described in the second aspect in electronic sensing, membrane separation, flexible devices, and biosensing.
[0027] Compared with the prior art, the beneficial effects of the present invention are reflected in:
[0028] The electrochemical system provided by this invention can prepare a uniform self-supporting silver nanofilm at the gas-liquid interface. By simply adjusting the deposition voltage and / or electrodeposition time during the electrochemical deposition process and controlling the voltage waveform during the electrodeposition process, the thickness and roughness of the silver film can be controlled in real time in situ.
[0029] The present invention also applies the above method to prepare silver nanoarrays. By setting different pulse voltage waveforms, a controllable silver nanoarray structure can be obtained. This self-supporting silver nanofilm with a special morphology is expected to be widely used in electronic sensing, membrane separation, flexible devices and biosensing. Attached Figure Description
[0030] Figure 1 This is a schematic diagram illustrating the evolution of the gas-liquid interface assembly structure, in which... Figure 1 A in the diagram is a schematic diagram of electrochemical deposition of silver film at the gas-liquid interface; Figure 1 B in the figure represents the ion density distribution of silver ions at the gas-liquid interface as simulated by molecular dynamics. Figure 1 In this context, C represents the change in the degree of order of silver ions during the cooling process, as simulated by molecular dynamics. Figure 1 D in the figure represents the Brewster angle microscopy characterization of the cooled "thin sheet" product. Figure 1 E in the image represents the SEM image of the cooled "thin sheet" product and its corresponding EDS image. Figure 1 In this context, F represents the energy of the system during the temperature change process. LJ Energy simulation results; Figure 1 G in the figure is the small-angle X-ray diffraction pattern of the "thin sheet" product after cooling, which verifies the change in the spacing of the multilayer structure.
[0031] Figure 2 The states of the electrolyte at different stages during the variable temperature pretreatment process (turbid - clear - translucent) are shown. State I is the turbid state of the electrolyte before heating; State II is the clear state of the electrolyte after heating; and State III is the translucent state of the electrolyte after cooling.
[0032] Figure 3 The transmittance, thickness, roughness, growth rate, and sheet resistance of self-supporting silver nanofilms obtained under different deposition voltages (5V, 10V, 15V) are statistically analyzed. Figure 3 In this context, A represents the transmittance of the self-supporting silver nanofilms obtained under different deposition voltages (5V, 10V, 15V). Figure 3 In this context, B represents the thickness and roughness of the self-supporting silver nanofilms obtained under different deposition voltages (5V, 10V, 15V). Figure 3 In the figure, C represents the statistical growth rate of self-supporting silver nanofilms under different deposition voltages (5V, 10V, 15V). Figure 3In this context, D represents the sheet resistance of the self-supporting silver nanofilms obtained under different deposition voltages (5V, 10V, 15V).
[0033] Figure 4 Optical photographs of silver nanofilms with periodic stripe patterns prepared by programming a voltage waveform (square wave) and the corresponding voltage waveform are shown. Figure 4 The optical photograph of the silver nanofilm with the letter "Z" in A and the Morse code information were used to design the corresponding voltage waveform; Figure 4 The optical photograph of the silver nanofilm with the letter "J" in B and the Morse code information were used to design the corresponding voltage waveform; Figure 4 The C in the image represents the letter "U". An optical photograph of the silver nanofilm and Morse code information were used to design the corresponding voltage waveform.
[0034] Figure 5 This is a three-dimensional interference microscope image showing the thickness variation of the silver film from high potential to low potential and then back to high potential.
[0035] Figure 6 The microstructure of the ridge-striped nanofilm and its corresponding voltage waveform are shown, among which, Figure 6 In the image, A represents a three-dimensional interference microscope image; Figure 6 In the image, B represents a photograph taken with an optical microscope; Figure 6 In this context, C represents the voltage waveform used to fabricate the structure. Figure 6 In the image, D represents the microscopic characterization image obtained by scanning electron microscopy.
[0036] Figure 7 A schematic diagram illustrating the transfer of silver nanofilms onto a flexible PDMS substrate and their application as a flexible SERS sensing patch is provided. Figure 7 In this context, A represents the application scenario of Ag / PDMS flexible SERS patch; Figure 7 In this context, B represents the FDTD simulation of the silver nanofilm; Figure 7 C in the SERS patch represents the Raman signal of different concentrations of rhodamine 6G (R6G). Figure 7 The value of D in the figure is 1361 cm. -1 Intensity correlation fitting of different concentrations of R6G under characteristic peak.
[0037] Figure 8 To demonstrate the transfer of a special silver nanofilm with a ridge-like stripe structure onto a PET substrate and to showcase its performance as a flexible pressure sensor, a schematic diagram is presented. Figure 8 A in the diagram is a schematic of a flexible pressure sensor; Figure 8 In this context, B represents the bending performance of the device. Figure 8 C in the figure represents the tensile properties of the device. Detailed Implementation
[0038] The following is a detailed description in conjunction with the accompanying drawings and embodiments.
[0039] This invention provides a method for preparing nanofilms at the gas-liquid interface using electrochemical deposition technology. Specifically, the method involves preparing an electrolyte composed of silver nitrate and sodium dodecyl sulfate (SDS), and altering the molecular layer arrangement at the interface through temperature variation treatment (first heating to 80°C and then cooling to 0°C), thereby reducing the nucleation energy barrier of the silver film at the gas-liquid interface. Figure 1 A). Molecular dynamics simulations of silver ion distribution at the gas-liquid interface show ( Figure 1 In the B section, after adding the anionic surfactant sodium dodecyl sulfate (SDS) to the silver nitrate (AgNO3) electrolyte, SDS dissociates into dodecyl sulfate ions (DS) in the solution. - ) and sodium ions, DS - Alkane chains with hydrophilic head groups and hydrophobic tail groups spontaneously arrange themselves at the gas-liquid interface, forming a negatively charged molecular layer. Positively charged silver ions accumulate at the gas-liquid interface due to electrostatic attraction. After cooling, the distribution of silver ions at the gas-liquid interface becomes even more concentrated. After subjecting the electrolyte to temperature-switching treatment (first heating and then cooling), DS... - The arrangement of the molecules has changed, becoming more ordered at the gas-liquid interface. Figure 1 C in the text), Brewster angle microscope ( Figure 1 D) and E in LJ Energy simulation results show that ( Figure 1 In the E), a phase transition occurred during the temperature change, generating thin sheets that floated at the gas-liquid interface (serving as a seed layer for self-supporting thin film growth in the preparation process); energy dispersive X-ray spectroscopy ( Figure 1 F in the figure) and small angle X-ray diffraction indicate that ( Figure 1 G in the thin film, metal ions (Ag) + ) and surfactant ions (DS) - The self-assembled structure at the gas-liquid interface forms an ordered and compact multilayer sandwich structure. Then, an electric field is applied, and under the guidance of this structure, the self-supporting nanofilm can undergo natural electrochemical growth along the single layer of surfactant arranged on the gas-liquid interface. The thickness and roughness of the film can be controlled by changing the voltage.
[0040] Electrochemistry is real-time; electrodeposition behavior changes with voltage. Since the thickness and roughness of films obtained under different voltages are different, novel microstructures can also be obtained during the transition between high and low voltages. Therefore, by controlling the voltage and time of electrodeposition, the complex microstructures of self-supporting nanofilms can be precisely designed. Understanding the film deposition behavior during voltage transition is crucial.
[0041] As the applied voltage increases, nucleation accelerates suddenly, electrodeposition moves forward more quickly, and the laterally grown film becomes thinner. Conversely, as the applied voltage decreases, the nucleation rate drops abruptly, thus significantly slowing lateral extension of the interface. Simultaneously, due to the accumulation of cations driven by the earlier higher voltage at the growth front, existing nuclei at the growth front become larger, forming a higher ridge. This ridge structure only appears when the voltage decreases.
[0042] Therefore, this invention also achieves morphological control of the microstructure of the self-supporting nanofilm by controlling the changes in deposition voltage at each step.
[0043] Example 1
[0044] A method for preparing self-supporting nanofilms by electrochemical deposition at the gas-liquid interface includes the following steps:
[0045] (1) The electrolyte consists of silver nitrate and sodium dodecyl sulfate (SDS). The final concentration of silver nitrate in the electrolyte is 30 mM, and the final concentration of sodium dodecyl sulfate (SDS) is 17 mM. First, the electrolyte is placed at 80°C. o Heat the electrolyte on the hot plate at C until it becomes clear and transparent. Take the clear and transparent electrolyte and place it in 0... o The solution was cooled in a refrigerator (C) for 20 minutes. The transmittance of the solution was monitored using a UV-Vis-NIR spectrophotometer. When the transmittance at 550 nm (the wavelength to which the human eye is most sensitive to light) reached 30%, the electrolyte was removed and used as the precursor solution for electrodeposition of a self-supporting silver film. The solution states and optical transmittance at different stages are shown below. Figure 2 As shown.
[0046] (2) Pour 50 mL of the prepared electrolyte (precursor solution) into a circular glass tank with a diameter of 6 cm. The electrolytic cell should be 100 mL in size. Use a carbon rod with a diameter of 5 mm as the anode and a piece of aluminum foil with a diameter of 25 mm × 75 mm as the cathode. Immerse them in the electrolyte in parallel with the electrode spacing of about 6 cm. Keep the electrodeposition temperature at room temperature to prepare a two-electrode system.
[0047] In the two-electrode system, a constant voltage mode of 10 V was applied. After 30 seconds, a silver spot appeared at the gas-liquid interface near the cathode and rapidly expanded into a film. The film front continued to grow outwards, and after about 6 minutes, the silver film completely covered the entire liquid surface.
[0048] (3) After plasma treatment of the optical glass plate and silicon wafer substrate to make their surfaces hydrophilic, place the substrate in a plasma cleaner and bombard it with plasma at a power of 80 W in an air atmosphere for 10 minutes. When the silver film grown on the gas-liquid interface covers the entire surface of the electrolytic cell, take the hydrophilic optical glass and silicon wafer substrate and retrieve the self-supporting silver film grown on the gas-liquid interface for later use.
[0049] (4) A plasma-treated optical glass plate and a silicon wafer were slowly inserted from below the thin film and then retrieved to obtain a silver film transferred onto the optical glass plate and the silicon wafer. Scanning electron microscopy revealed that the thin film was composed of interwoven nanodendritic structures with a width of 20 nm, forming a porous network structure with a thickness of 100 nm. The thin film exhibited good self-support and flexibility. Spectroscopy measured by a UV-Vis-NIR spectrophotometer showed that the silver film prepared at 10V had a transmittance of approximately 60% at a wavelength of 550 nm. Figure 3 Figure A shows the transmittance curve of the silver film in the visible light region (380 nm-800 nm).
[0050] Example 2
[0051] (1) Repeat steps 1 and 2 of Example 1 to prepare the same precursor electrolyte and two-electrode system. Electrochemical deposition was performed using constant voltages of 5V, 10V and 15V respectively (other conditions were the same as in Example 1).
[0052] (2) The film thickness, roughness, and sheet resistance can all be adjusted by voltage, such as Figure 3 As shown in Figure BD, at a deposition voltage of 5V, the film growth rate is slow (0.17 mm / s), resulting in a thicker film with a coarser dendritic structure as observed by SEM. The average thickness measured by 3D profilometry is 495 nm, with a transmittance of approximately 25% and a sheet resistance of approximately 76 Ω / sq. At a deposition voltage of 15V, the film growth rate is fastest (0.3 mm / s), resulting in the thinnest film. The average thickness is 63 nm, the transmittance increases to 70%, and the sheet resistance is 520 Ω / sq.
[0053] This embodiment demonstrates that continuous and reversible control of film thickness, structure, and optoelectronic properties can be achieved by simply adjusting the deposition voltage.
[0054] Example 3
[0055] (1) Repeat steps 1 and 2 of Example 1 to prepare the same precursor electrolyte and two-electrode system.
[0056] (2) Establish the correspondence between potential and transparency. Use 5V, 10V and 15V to represent “——”, “·” and “ / / (space)” in Morse code, respectively. The preset potential waveform (i.e. “digital information”) can be encrypted into the longitudinal stripes of the nanofilm. The corresponding voltage waveform is designed according to the Morse code information of the letters “Z”, “J” and “U”. The striped silver film covering different encryption information (the voltage waveforms of 5V, 10V and 15V are combined as needed) can be directly prepared.
[0057] (3) After deposition, a large-area silver film with alternating light and dark stripes was obtained. Measurements using an optical microscope and thickness profiler confirmed that the film's transmittance curve exhibited periodic fluctuations corresponding to the voltage waveform period, thus realizing the encoding of "electrical signals" into "optical structures" (such as...). Figure 4 As shown in the figure, this is a new way of combining electrochemical processes with information storage.
[0058] Example 4
[0059] (1) Repeat steps 1 and 2 of Example 1 to prepare the same precursor electrolyte and two-electrode system.
[0060] (2) Use the prepared precursor solution as the electrolyte and set a continuous step potential from high potential to low potential and then back to high potential. The specific deposition voltage parameters are 5V - 2V - 5V, and the voltage is applied for 2s at each stage.
[0061] Three-dimensional interferometric microscopy images of the deposited silver film are as follows: Figure 5 As shown, when the potential steps from high (5V) to low (2V), the reaction kinetics drop sharply, and a large amount of Ag that has been generated but not embedded in the crystal lattice is released. 0 Atoms accumulate at the growth front, leading to abnormal growth perpendicular to the film surface, forming a "ridge" structure. The thickness then tends to stabilize, and the ridge structure only appears when the voltage decreases. Conversely, when the potential jumps from low (2V) to high (5V), the nucleation rate at the growth front suddenly increases, and the film thickness decreases.
[0062] (3) Set up an alternating pulse voltage waveform of 5V and 0V with a pulse duration of 0.5s, and characterize the prepared silver nanofilm, such as... Figure 6 As shown in the three-dimensional interference microscopy results in Figure A, the silver nanofilm has a continuous ridge-like stripe structure with a stripe (ridge) spacing of 50 mm and a stripe (ridge) height of 300 nm. The morphological undulations are consistent with those obtained from optical microscopy. Figure 6 (B in the text) and scanning electron microscope ( Figure 6 The results in D are consistent, and each stripe pattern corresponds to the set voltage pulse waveform. Figure 6 (C in the middle).
[0063] Application Example 1
[0064] Ag nanofilms deposited at 10 V were prepared according to the method in Example 1. Polydimethylsiloxane PDMS prepolymer (Dow Corning DC184) was mixed at a mass ratio of 10:1, spin-coated into a film, and cured at 60 °C to obtain a flexible PDMS substrate with a thickness of approximately 100 μm. The PDMS substrate was subjected to oxygen plasma treatment to make its surface hydrophilic (see step 3 of Example 1 for specific steps), and then used to retrieve the silver film at the gas-liquid interface. After natural drying, a flexible SERS patch was obtained.
[0065] like Figure 7 As shown in A, the silver film surface of the patch was directly pressed onto the surface where droplets of different concentrations (1×10⁻⁶) were dropped. -5 Up to 1×10 -9 The solution (mol / L) of R6G was applied to apple peel, exposed for 5 seconds, then removed and subjected to Raman spectroscopy. Figure 7 As shown in C, even at a low of 1×10 -9 At a concentration of mol / L, the characteristic Raman peaks of R6G molecules can still be clearly detected, with a high signal-to-noise ratio and good spectral reproducibility; Figure 7 The D in the figure indicates that within the concentration range (1×10⁻⁶), -5 Up to 1×10 -9 The intensity of the R6G characteristic peak (mol / L) showed a good linear relationship with concentration, with a linear regression coefficient R² of 0.95, indicating that the SERS patch has reliable quantitative detection potential. These results not only verify the feasibility of using this flexible SERS patch for in-situ, non-destructive molecular detection on complex surfaces (e.g., fruit peel), but also demonstrate that it overcomes the technical difficulties of traditional rigid SERS substrates, such as difficulty in fitting curved surfaces and large signal fluctuations, in terms of preparation process, signal stability, and detection sensitivity, providing a reliable platform for trace detection in practical samples.
[0066] Application Example 2
[0067] Ag nanofilms with a spacing of 50 mm were prepared according to the method in Example 4. Striped Ag nanofilms with periodic nanoridges were then prepared using potential waveform programming and transferred onto a flexible polyethylene terephthalate (PET) substrate to obtain the desired result. Figure 8 The resistive pressure sensor shown in Figure A. The nanoridges introduce regular structural asymmetry. In tests with bending angles ranging from 0° to 180° ( Figure 8 In section B), when the bending direction is parallel to the nanoridges, the ridge structure mainly undergoes cooperative deformation, with minimal change in resistance. However, when the bending direction is perpendicular to the nanoridges, relative slippage occurs between the ridges, altering the contact state and significantly affecting the conductive pathway, leading to a large change in resistance. Similarly, in tensile tests (… Figure 8 The resistance change caused by stretching perpendicular to the ridge direction (C) is much greater than that in the parallel direction. This strong anisotropic response enables the sensor to distinguish mechanical stimuli from different directions, providing a new approach for designing electronic skin or human-machine interfaces with orientation recognition capabilities.
[0068] The technical solution of the present invention has been described above by way of example. It should be noted that, without departing from the core of the technical solution, any simple modifications, alterations or other equivalent substitutions that can be made by those skilled in the art without creative effort fall within the protection scope of this application.
Claims
1. A method for preparing a self-supporting nanofilm by electrochemical deposition at a gas-liquid interface, characterized in that, Includes the following steps: (1) Prepare an electrolyte containing silver salt and surfactant, and subject the electrolyte to variable temperature pretreatment to induce the formation of a metastable solution at the gas-liquid interface. The electrolyte is composed of silver nitrate with a final concentration of 25-30 mM and sodium dodecyl sulfate with a final concentration of 10-17 mM. The variable temperature pretreatment of the electrolyte is specifically as follows: the electrolyte is heated to 70-90°C, kept at the temperature until the solution is clear and transparent, and then cooled to 0-5°C for 15-25 minutes to obtain a translucent or turbid metastable solution with crystals floating at the gas-liquid interface. (2) Using the pretreated electrolyte as the working medium, a carbon rod as the anode and an aluminum foil as the cathode are immersed in the electrolyte in parallel, and an electrochemical deposition is performed by applying a voltage at room temperature. The voltage is a constant voltage or a pulse voltage. (3) Silver ions are reduced in situ at the gas-liquid interface and spontaneously grow to form a self-supporting nanofilm covering the gas-liquid interface.
2. The preparation method according to claim 1, characterized in that, In step (2), the constant voltage is 2~30V and the deposition time is 30~60 seconds.
3. The preparation method according to claim 1, characterized in that, In step (2), the waveform of the pulse voltage can be controlled by programming to prepare a nanofilm with periodic stripes, regions of different thicknesses, or a preset nanoridge structure.
4. The preparation method according to claim 1, characterized in that, In step (2), a self-supporting silver nanofilm with periodic stripes can be obtained by setting the pulse voltage waveform that alternates between 5V and 0V. Here, 5V is defined as the growth voltage, 0V is defined as the stop voltage, the height of the stripes is determined by the application time of the stop voltage, and the width of the stripes is determined by the application time of the growth voltage.
5. A self-supporting nanofilm prepared by the preparation method according to any one of claims 1-4.
6. A self-supporting nanofilm composite material, characterized in that, The invention comprises the self-supporting nanofilm of claim 5, and a substrate supporting the nanofilm; the substrate is selected from silicon wafers, glass sheets or flexible polymer substrates; the substrate is subjected to oxygen plasma treatment to make its surface hydrophilic before being combined with the self-supporting nanofilm.
7. A flexible patch, characterized in that, The invention comprises the self-supporting nanofilm of claim 5, and a poly(p-phenylene dimethylsiloxane) polymer substrate supporting the nanofilm; the substrate is subjected to oxygen plasma treatment to make its surface hydrophilic before being bonded to the nanofilm.
8. The application of the self-supporting nanofilm according to claim 5 in electronic sensing, membrane separation, flexible devices and biological detection.
Citation Information
Patent Citations
Preparation method and application of silver nanoparticles with universal dispersion characteristic
CN114101656A